Genetic Differentiation for Gene Diversity among Pearl Millet (Pennisetum glaucum (L.) R. Br.) Landraces As Revealed by SSR Markers - Lardia Ali Bougma; Mahamadi Hamed Ouédraogo; Adjima Ouoba; Abdou Azaque Zouré; Nerbéwendé Sawadogo; Mahamadou Sawadogo (International Journal of Agronomy)
Pearl millet (Pennisetum glaucum) is one the most important crops in Burkina Faso. Knowledge of the genetic parameters of different pearl millet landraces grown in Burkina Faso is of great importance for improvement and breeding programs of pearl millet. In this study, 20 pairs of SSR markers were used to compare and analyze the genetic diversity of 86 landrace populations. Results show a total of 67 alleles detected and each locus varies between 2 and 6 with an average of 4 alleles per marker. The probability to having two different alleles per locus was 0.61. The values of genetic diversity parameters of pearl millet populations from the northern region of the country were higher than those from the others regions. The analysis indicates that, over time, alleles are lost and new alleles are added. Analysis of molecular variance showed genetic variation was primarily a function of differences in cultivated populations. Most pairwise FST comparisons between provenances were at a statistically significant level. Our study will provide a scientific basis for the effective management and utilization of germplasm resources of pearl millet populations.